1998
DOI: 10.1002/(sici)1099-1387(199805)4:3<195::aid-psc141>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

PEGA supports for combinatorial peptide synthesis and solid-phase enzymatic library assays

Abstract: Permeable resins cross-linked with long PEG chains were synthesized for use in solid-phase enzyme library assays. High molecular weight bis-amino-polyethylene glycol (PEG) 4000, 6000, 8000 were synthesized by a three-step reaction starting from PEG-bis-OH. Macromonomers were synthesized by partial or di-acryloylation of bis-amino-PEG derivatives. Bis/mono-acrylamido-PEG were copolymerized along with acrylamide by inverse suspension copolymerization to yield a less cross-linked resin (Type I, compounds 6-9). Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…We found that the non-functionalized PEG microbeads were more compatible with various solvents due to the increase in amphiphilicity [22]. Compared with commercially available PEG-based microbeads, such as PEGA resin [23,24], TentaGel XV resin [25,26], and ChemMatrix resin [27,28], PEG-amine hydrogel microbeads did not swell relatively with various solvents because of the high degree of crosslink [4,5]. However, our PEG-amine microbeads did not need a high swelling ratio because most of the active functional groups were exposed at the shell region [22,29].…”
Section: Resultsmentioning
confidence: 98%
“…We found that the non-functionalized PEG microbeads were more compatible with various solvents due to the increase in amphiphilicity [22]. Compared with commercially available PEG-based microbeads, such as PEGA resin [23,24], TentaGel XV resin [25,26], and ChemMatrix resin [27,28], PEG-amine hydrogel microbeads did not swell relatively with various solvents because of the high degree of crosslink [4,5]. However, our PEG-amine microbeads did not need a high swelling ratio because most of the active functional groups were exposed at the shell region [22,29].…”
Section: Resultsmentioning
confidence: 98%
“…Here we demonstrated the feasibility of using glass, agarose and TentaGel® beads for Bead-GPS, although other bead types that are commonly used for libraries may also be compatible (e.g. PEGA 30 acrylamide-PEG co-polymer beads). While further study is needed comparing these different bead types, several factors appear to affect the ability to obtain strong MALDI-MSI signals, well-defined spot morphology and to measure functional interaction of prey biomolecules (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The highly permeable nature of the SPOCC resin allows enzymes to diffuse into the polymer matrix and perform chemical reactions 10. 18 It was possible to inhibit the enzymatic activity of trypsin by using EETI‐II that had been synthesized and folded on the SPOCC resin, thus demonstrating the ability of trypsin to diffuse into the resin. The enzyme and inhibitor can also be recovered from the resin after TFA cleavage.…”
Section: Methodsmentioning
confidence: 99%